Near-infrared light triggered shape memory and self-healable polyurethane/functionalized graphene oxide composites containing diselenide bonds. (5th December 2018) - Du, Weining; Jin, Yong; Lai, Shuangquan; Shi, Liangjie; Fan, Wuhou; Pan, Jiezhou
Abstract: In this work, polyurethane/functionalized graphene oxide composites containing diselenide bonds were fabricated by covalently incorporating functionalized graphene oxide (FGO) into hydroxyl-terminated polyurethane prepolymers via in-situ polymerization. It was found that the isocyanate terminated molecules were covalently attached onto the graphene oxide surface, and the FGO could act as a multifunctional reinforcer in mechanical and photo-thermal properties of polyurethane composites. Significant enhancements of mechanical, thermal transport, and crystallization performances of composites were observed with the incorporation of 2 wt% of FGO. Due to the photo-thermal and crystallization-induced effects of FGO as well as the exchangeable characteristic of diselenide bonds, the PID-FGO2 composite exhibited both shape memory and repeatable self-healing functions upon exposure to near infrared (NIR) irradiation. In particular, the introduction of diselenide bonds could greatly improve the healing efficiency from ∼45% to ∼90%, and the healing efficiencies were maintained above 75% even after five healing cycles. Such favorable healing is acquired by the photo-thermal response, shape memory effect, and diselenide exchange reaction simultaneously, and the shape memory effect is of great importance for assisting the healing process. We expect that this work could provide a viable avenue for multifunctional composite materials. Graphical abstract: Highlights: Polyurethane/functionalized graphene oxide (FGO) composites containing diselenide bonds were fabricated. Properties of composites were significantly enhanced with the incorporation of 2 wt% of FGO. PID-FGO2 composite exhibited both shape memory and repeatable self-healing functions under near infrared light. Self-healing behavior was achieved by the photo-thermal, shape memory effect, and diselenide metathesis simultaneously. Further addition of diselenide bonds could effectively strengthen the healing efficiency.